Laptops all-in-one for dummies - Sandler, Corey. 1950- (For Dummies, 2010)
The all-in-one guide to buying, using, securing, and transporting a laptop-it's ten books in one! If you want to take a computer with you on a trip, to a coffee shop, or into the kitchen when you're cooking, laptops are just the ticket.